Analysis Of Factors Affecting Poverty In The Special Region Of Yogyakarta In 2017-2022 - Agnes Ratih Ari Indriyani; Deni Kunta Mahendra (International journal of technology and education research, 2024)
This research aims to determine the influence of the Human Development Index, Gross Regional Domestic Product and Unemployment on poverty in D.I. Yogyakarta 2017-2022. This research uses samples of poverty, HDI, GRDP and Unemployment data from 5 districts/cities in D.I. Yogyakarta over a period of 6 years, namely 2017 to 2022. The method used in the research is quantitative using secondary data sourced from data from the Central Statistics Agency. Data were analyzed using panel data analysis using the Fixed Effect Model (FEM). The research results showed that the Human Development Index variable (X1) showed a negative sign and was not significant for poverty in D.I. Yogyakarta, the Gross Regional Domestic Product variable (X2) shows a negative sign and is not significant for poverty in D.I. Yogyakarta and the Unemployment variable (X3) shows a positive and significant sign of poverty in D.I. Yogyakarta. Simultaneously, the variables Human Development Index, Gross Regional Domestic Product and Unemployment together influence poverty in D.I. Yogyakarta.